Liquidity, term spreads and monetary policy - Yunus Aksoy; Henrique S. Basso (Center for Economic Studies and ifo Institute (CESifo), 2012)
We propose a model that delivers endogenous variations in term spreads driven primarily by banks' portfolio decision and their appetite to bear the risk of maturity transformation. We first show that fluctuations of the future profitability of banks' portfolios affect their ability to cover for any liquidity shortage and hence influence the premium they require to carry maturity risk. During a boom, profitability is increasing and thus spreads are low, while during a recession profitability is decreasing and spreads are high, in accordance with the cyclical properties of term spreads in the data. Second, we use the model to look at monetary policy and show that allowing banks to sell long-term assets to the central bank after a liquidity shock leads to a sharp decrease in long-term rates and term spreads. Third, such interventions have significant impact on long-term investment, decreasing the amplitude of output responses after a liquidity shock. The short-term rate does not need to be decreased as much and inflation turns out to be much higher than if no QE interventions were implemented. Finally, we provide macro- and microeconometric evidence for the U.S. to show the importance of expected financial business profitability in the determination of term spread fluctuations.
Keywords: E43; E44; E52; G20; 330; yield curve; quantitative easing; financial business profits; bank portfolio; Zinsstruktur; Geldpolitik; Bank; Portfolio-Management; Rentabilität; Theorie; USA